Sanksi Pidana bagi Pelaku Penyelundupan Imigran Gelap - Anak Agung Ngurah Alit Bramandhita; I Wayan Arthanaya; Ni Made Sukaryati Karma (Jurnal Konstruksi Hukum, 2020)
The smuggling of illegal immigrants in Indonesia is an old problem, compounded by the situation in which people smuggling is carried out by Indonesian citizens themselves. The weak law regarding smuggling of illegal immigrants owned by Indonesia has made Indonesia no longer a transit country, but has become a smuggling destination country. Illegal immigrant smuggling can be defined as an activity that has the aim of making a profit, by bringing illegal foreigners to enter Indonesian territory. This study aims to determine the application of the illegal immigrant smuggling crime in Indonesia and to know the criminal sanctions against the illegal immigrant smugglers. This type of research used in this research is normative legal research using the literature review method in finding legal material. The data sources are Primary Legal Materials, which are binding legal materials, namely the 1945 Constitution of the Republic of Indonesia, the RKUHP in Chapter XXII of human smuggling, the Law concerning. The data was collected by means of a documentation study which was carried out by reading and recording the explanatory information obtained. The materials that have been collected are then processed using the inductive deductive method or vice versa, in order to obtain quality legal materials in accordance with the subject matter discussed which in the end the processing will be presented descriptively. The results show that the illegal immigrant smuggling crime is regulated in Article 120 of Law Number 6 of 2011. Then, the perpetrator of the illegal immigrant smuggling crime will be imprisoned for a minimum of 5 (five) years and a maximum of 15 (fifteen) years with a minimum fine of five hundred million rupiah and a maximum of one billion five hundred million rupiah.